Eduquality : human centered quality management in education : a model for deployment, assessment, and sustainability - Lepeley, Maria-Teresa (Emerald Publishing Limited : IAP/Information Age Publishing, Inc., 2019)
We, educators, are often so involved in daily teaching duties that lack time to absorb the broader picture of what is happening beyond our classrooms in a rapidly changing world. That is the norm in our profession. But our responsibility is to constantly improve the wellbeing of all the students enrolled in our classes. Education is the most important and most challenging profession there is. Educators shape future leaders, heroes, and people who can improve the world. Transformational educators have long term effects in the lives of students that projects on nations. On the opposite side, students waste time sitting in a classroom and can hamper future opportunities in life when educators fail to motivate them to assume responsibility for improving their wellbeing and build a better world for all.Education is not just another profession, it is an extraordinary endeavor with surmounting human responsibility to transform lives for the better.To claim the merit of education, educators must project education beyond school border into the context of society and the economy. To miss this context is a pending challenge. We, educators, need to earn the merit we deserve. But we now know that we earn merit with knowledge how to manage for quality and continuous improvement aiming at results leading to sustainability and working systematically to reach high standards.Lepeley, author of numerous publications on the subject, former examiner of the US Baldrige National Quality Award and adviser to NQAs in six countries in Latin America, presented her quality management model for education in the World Bank Global Network in the early 2000's. Her model has pioneered integration of education with other disciplines and other sectors projecting the importance and impact of education on sustainable development. The author emphasizes that neglecting the surmounting demand for quality will impair education as a fundamental factor of development, harm the worth of educators, undermine the profession and dent the wellbeing of human beings in inclusive nations and a peaceful world.
Keywords: Education -- Standards.; Education -- Administration -- General.; Education.; Educational administration and organization.; elektronické knihy; electronic books